Sounds and Voices from the Past. Using archive material in radio music shows: Special section: RadioMusic. Papers from the LARM conference ‘Digital Archives, Audiovisual Media and Cultural Memory’ Copenhagen, 14–15 November 2013 - Vad, Mikkel (Danish Yearbook of Musicology, 2016)
The article is a critical engagement with the construction of cultural memory and performance of liveness when using archive material in radio shows and is based on the author’s experience as a radio presenter. Theoretically it is framed by Aleida Assmann’s concepts of storage memory and functional memory. Firstly, a show presenting historical concert recordings of classical music, the ‘P2 Gold Concert’, is analysed to show how radio presenters emphasize liveness to eliminate the historicity of the recording. However, such evocation of liveness is only possible because of the recorded nature of the archive material. Secondly, a show presenting archived interviews, reports, features, etc. of jazz music and musicians, ‘From the Archive’, is analysed with particular regard to how a virtual soundscape or mise-en-sc.ne of ‘old’ technology is created to perform an imaginary archive and how the archive is fetishized. Again, this presentation and the values it holds is only possible because of the recorded, mediatized nature of the archive material. Thus, in both shows the presenter uses fi ctionalizing strategies of performance to present the archive material, and these strategies in fact highlight the disjunctures and connections between storage memory and functional memory.